Puzzle Food Warmer / Jumaelya Jogeran … [et al.] - Jogeran, Jumaelya; Yaakob, Hafisah; Suhaimie, Intan Liana; Sehat, Nani Shuhada; Daud, Siti Rohana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This food heater is created for office workers (or urban nomads always on the go) who do not even have time to heat their lunch in the microwave oven during their lunch time. Besides, it also suitable for students who studying late in campus and this food warmer can heat up canned food or food they bought earlier. It also suitable for outdoor camping trips. This product also can reduce the troubles of using burners and easy to be cleaned. This uniqueness of this food warmer is come with plenty of space to heat food without affecting other food in the same box. This product has the potential to be commercialized in the near future.